PROSTHODONTIC TREATMENT IN THE ELDERLY, WHAT DENTISTS KNOW - Gabriella Gabriella; Isya Hanin (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Tooth loss is most experienced by the elderly population. The number of elderly people is increasing in Indonesia in direct proportion to the increase in cases of tooth loss. Tooth loss can be treated with prosthodontic treatment performed by dentists, so dentists need to have sufficient knowledge and skills. Objectives: To get an overview of the knowledge of dentists who graduated from the Faculty of Dentistry, Trisakti University in 2017-2019 regarding prosthodontic treatment in the elderly. Methods: This study uses a descriptive observational method with a cross-sectional type. The measuring tool uses a questionnaire via google form containing 25 questions adopted from foreign journals with similar research that was tested for validity and reliability. After being tested, 21 valid and reliable questions were filled by 89 respondents. Data collection is carried out online and the data is presented in the form of a frequency distribution. Results: The highest average score (mean) obtained was 41, while the lowest average score (mean) obtained was 29. The average score (mean) that most respondents obtained was 39 with the average value (mean) of respondents 92.86%. Conclusion: The average score (mean) obtained is 37.12 with a maximum score of 42. The average value (mean) of respondents is 88.38%. Dentist's knowledge of prosthodontic treatment in the elderly is good. Keywords: Dentist, Elderly, Knowledge, Prosthodontics